2021
DOI: 10.1002/ajb2.1738
|View full text |Cite
|
Sign up to set email alerts
|

“Diminishing returns” for leaves of five age‐groups of Phyllostachys edulis culms

Abstract: Premise: Leaf mass (M) and lamina surface area (A) are important functional traits reported to obey a scaling relationship called "diminishing returns" (i.e., M ∝ A α>1 ). Previous studies have focused primarily on eudicots and ignored whether the age of leaves affects the numerical value of the scaling exponent (i.e., α). Methods: The effect of age was examined using 1623 Phyllostachys edulis leaves from culms differing in age collected in Nanjing, China. The scaling relationships among leaf A, fresh mass (FM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Leaves are the most active and primary photosynthetic plant organ (Elser et al, 2010 ; Yang et al, 2019 ), their size and structure exhibit a tradeoff between the support cost and photosynthetic returns during plant adaptation to environmental changes (Shi et al, 2020 , 2022 ; Guo et al, 2021 ; Li et al, 2022a , b ), and leaf stoichiometry can reflect the tradeoff formed in this evolution from the angle of leaf chemical elements and its spatio-temporal variations (Baxter and Dilkes, 2012 ; Cao et al, 2020 ; Zhu et al, 2020 ). Leaf C/N and C/P were widely accepted as effective indicators of plants' N and P use efficiency and growth rate, and their lower values indicated lower nutrient utilization efficiency and higher plant growth (Weidner et al, 2015 ; Sun et al, 2017 ; Cao et al, 2020 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Leaves are the most active and primary photosynthetic plant organ (Elser et al, 2010 ; Yang et al, 2019 ), their size and structure exhibit a tradeoff between the support cost and photosynthetic returns during plant adaptation to environmental changes (Shi et al, 2020 , 2022 ; Guo et al, 2021 ; Li et al, 2022a , b ), and leaf stoichiometry can reflect the tradeoff formed in this evolution from the angle of leaf chemical elements and its spatio-temporal variations (Baxter and Dilkes, 2012 ; Cao et al, 2020 ; Zhu et al, 2020 ). Leaf C/N and C/P were widely accepted as effective indicators of plants' N and P use efficiency and growth rate, and their lower values indicated lower nutrient utilization efficiency and higher plant growth (Weidner et al, 2015 ; Sun et al, 2017 ; Cao et al, 2020 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For Model-1, -3, and -5 in Table 2, there are fixed slopes of 1, 2, and 2 on a log-log plot. Log-log plots were used because the distribution of leaf area is usually slightly skewed, and so log-transformation helps to normalize the data (Shi et al, 2019a;Yu et al, 2020;Guo et al, 2021). The bootstrap percentile method was used to calculate the 95% confidence interval (CI) of the difference in the estimated MP values between each pair of the nine studied species (Efron & Tibshirani, 1993;Sandhu et al, 2011).…”
Section: Models and Statistical Analysismentioning
confidence: 99%
“…The leaf is crucial to the growth and development of plants, with the characteristics and variation of leaf structure directly affecting absorption and utilization of light energy and nutrients ( Smith et al, 1997 ; Daas-Ghrib et al, 2011 ). Previous studies have shown that there is a tradeoff between the photosynthetic returns from increasing lamina area and the investment in leaf physical support and hydraulic systems from increasing lamina mass ( Niklas et al, 2007 ; Huang et al, 2019a , b , 2020 ; Guo et al, 2021 ). Lamina thickness and leaf shape have been demonstrated to affect such a tradeoff ( Niinemets et al, 2007 ; Lin et al, 2018 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%